Effects of heat acclimation on endurance capacity and prolactin response to exercise in the heat - Burk, A.; Timpmann, S.; Kreegipuu, K.; Tamm, M.; Unt, E.; Ööpik, V. (European Journal of Applied Physiology, 2012)
We examined the effect of heat acclimation (HA) on endurance capacity and blood prolactin (PRL) response to moderate intensity exercise in the heat in young male subjects (n = 21). Three exercise tests (ET) were completed on a treadmill: H1 (walk at 60% VO2peak until exhaustion at 42°C), N (walk at 22°C; duration equal to H1) and H2 (walk until exhaustion at 42°C after a 10-day HA program). Heart rate (HR), skin (T sk) and core (T c) temperatures and body heat storage (HS) were measured. Blood samples were taken immediately before, during and immediately after each ET. HA resulted in lower HR, T sk, T c and HS rate (P < 0.05) during ET, whereas endurance capacity increased from 88.6 ± 27.5 min in H1 to 162.0 ± 47.8 min in H2 (P < 0.001). Blood PRL concentration was lower (P < 0.05) during exercise in H2 compared to H1 but the peak PRL level observed at the time of exhaustion did not differ in the two trials. Blood PRL concentration at 60 min of exercise in H1 correlated with time to exhaustion in H1 (r = -0.497, P = 0.020) and H2 (r = -0.528, P = 0.014). In conclusion, HA slows down the increase in blood PRL concentration but does not reduce the peak PRL level occurring at the end of exhausting endurance exercise in the heat. Blood PRL response to exercise in the heat in non-heat-acclimated subjects is associated with their endurance capacity in the heat in a heat-acclimated state.